Fostering digital transformation in education: technology enhanced learning from professors’ experiences in emergency remote teaching - Mondragon-Estrada, Enrique; Kirschning, Ingrid; Nolazco-Flores, Juan Arturo; Camacho-Zuñiga, Claudia (Frontiers in Education, 2023)
In this work, we aim to understand professors’ perception on the key competences as well as the best educational strategies, and technological tools to guide Digital Transformation (DT) in education, according to their experience in Emergency Remote Teaching (ERT). In recent years, technological advancement has driven DT in many areas, education among them. ERT due to COVID-19 accelerated this transition. Restrictions and lockdowns forced higher education institutions to adopt remote teaching strategies and tools suited for a digital environment. We surveyed 100 professors from a private Mexican university, with 15-month experience of online ERT. We asked them through Likert scale questions to self-evaluate their performance and whether they perceived it to be better in online or hybrid environments compared to face-to-face environments in different aspects. We performed correlation, cluster, and factor analysis to identify relations and patterns in their answers. We also asked the participants through open-ended questions about the challenges and achievements they experienced, and the educational strategies and technological tools they successfully incorporated during ERT. We also conducted text mining to extract the most relevant information from these answers and validated that they were not polarized with negative sentiment using a Large Language Model. Our results showed social intelligence as an underlying competence for teaching performance that was highlighted in the digital environment due to the physical interaction limitations. Participants found success in implementing Information and Communication Technologies, resulting in maintaining student interest, and building trust in the online environment. Professors recognized the relevance not only of Learning Management Systems and communication platforms, as expected, but also hardware such as tablets, cameras, and headphones for the successful delivery of education in a digital environment. Technology Enhanced Learning spreads game-based, quizzing practices and collaborative learning to digital environments. Furthermore, professors recommend Learning-by-doing, Flipped Learning, Problem-based Learning, Game-based Learning and Holistic Education as some pedagogical methodologies that were successfully applied in ERT and could be implemented towards DT. Understanding the gains concerning teaching-learning strategies and technologies that were incorporated during ERT is of the utmost importance for driving DT and its benefits to current and future education.